WIND ENERGY DEVELOPMENT IN SUB-SAHARAN AFRICA: APPLICATION OF THE SATSA FRAMEWORK - Ameen, Ahmed; Lalk, Jorg (The South African Journal of Industrial Engineering, 2019)
There is a need for a framework that can be applied to wind energy developments in the sub-Saharan African (SSA) context that will facilitate technology-sustainable assessments to promote wind energy. This paper applies such a framework to potential wind energy developments in Namibia and Mozambique. In addition, the use of a system dynamics approach allows for wind turbine and power considerations to be adequately integrated into the application of the framework. The study applies the framework to both these countries to develop an outlook for potential wind energy developments. This results in the identification of key success factors.